An Analysis Of Health Promotion Strategies For Stunting Reduction In The Operational Area Of Minanga Public Health Center, Manado City - Claudia Wattie; Erwin Kristanto; Erling David Kaunang (CV. Inara, 2025)
Background:Stunting remains a significant public health challenge in Indonesia, including in Manado City. Despite various government initiatives, the prevalence of stunting persists due to complex contributing factors such as poor nutrition, inadequate parenting, and limited access to health services.Objective:This study aimed to analyze the implementation of health promotion strategies—specifically advocacy, social support, and community empowerment—in reducing stunting prevalence in the working area of Puskesmas Minanga, Manado.Methods:A qualitative study with an exploratory design was conducted from June to July 2025. Data were collected through in-depth interviews, direct observations, and document analysis involving 10 purposively selected informants: program managers, community leaders, and mothers of under-five children. Data were analyzed using content analysis guided by the Miles and Huberman model, involving data reduction, display, and conclusion drawing.Results:The findings revealed that (1) advocacy was carried out through mini-workshops and coordination with local stakeholders, although policy support and budgeting remained limited; (2) social support involved active participation of religious and community leaders in encouraging healthy practices, yet lacked formal community-based structures; and (3) community empowerment focused on cadre training and health education through monthly Posyandu activities, though constrained by funding and attendanceissues.Conclusion:Health promotion strategies—when applied in an integrated manner—showed potential to reduce stunting prevalence. However, sustainability depends on stronger policy commitment, consistent funding, and wider community involvement. Strengthening intersectoral collaboration and community ownership is essential to enhance the effectiveness of stunting prevention programs.